1992
DOI: 10.1111/j.1558-5646.1992.tb02074.x
|View full text |Cite
|
Sign up to set email alerts
|

PERFORMANCE OF TADPOLES FROM THE HYBRIDOGENETIC RANA ESCULENTA COMPLEX: INTERACTIONS WITH POND DRYING AND INTERSPECIFIC COMPETITION

Abstract: Abstract.»-The performance of three genotypes (LL, LR, RR) oftadpoles resulting from the hybrid mating system of Rana lessonae (phenotype L, genotype LL) and Rana esculenta (phenotype E, genotype LR) was determined in artificial ponds. The effects of interspecific competition and pond drying on growth, development, and survival of tadpoles were used to measure the performance of genotypes and the relative fitness of offspring. Among the three genotypes, tadpoles from the homogametic mating RR had the lowest su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 19 publications
1
70
1
Order By: Relevance
“…Besides nonrandom mating (Abt and Reyer 1993;Bergen et al 1997;Roesli and Reyer 2000;Som et al 2000;Engeler and Reyer 2001), differential survival after metamorphosis could, to a certain extent, counterbalance the hybrid's initial advantage and allow R. lessonae to catch up with it in numbers. However, in contrast to the numerous studies on larval development and survivorship to metamorphosis (e.g., Wilbur 1980;Smith 1983;Riis 1991;Semlitsch and Reyer 1992a;Rowe and Dunson 1995), relatively little is known about dynamics after metamorphosis (Sjögren 1988(Sjögren , 1991Berven 1990;Neveu 1991). Since water frogs are reported to live to 6 or even 12 years of age, depending on the region they come from (Günther 1990;Sjögren 1991), the influence of adult survival is not to be neglected, and information on mortality is needed to understand population processes in these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides nonrandom mating (Abt and Reyer 1993;Bergen et al 1997;Roesli and Reyer 2000;Som et al 2000;Engeler and Reyer 2001), differential survival after metamorphosis could, to a certain extent, counterbalance the hybrid's initial advantage and allow R. lessonae to catch up with it in numbers. However, in contrast to the numerous studies on larval development and survivorship to metamorphosis (e.g., Wilbur 1980;Smith 1983;Riis 1991;Semlitsch and Reyer 1992a;Rowe and Dunson 1995), relatively little is known about dynamics after metamorphosis (Sjögren 1988(Sjögren , 1991Berven 1990;Neveu 1991). Since water frogs are reported to live to 6 or even 12 years of age, depending on the region they come from (Günther 1990;Sjögren 1991), the influence of adult survival is not to be neglected, and information on mortality is needed to understand population processes in these species.…”
Section: Introductionmentioning
confidence: 99%
“…In populations without R. ridibunda, the two interspecific matings (LL × LR and LR × LL) result in R. esculenta, whereas the two intraspecific matings result in either R. lessonae (LL × LL) or nonviable R. ridibunda tadpoles (RR × RR). This, plus the fact that R. esculenta is superior to R. lessonae in terms of female fecundity (Berger 1977;Berger and Uzzel 1980) and tadpole survival (Heusser and Blankenhorn 1973;Semlitsch and Reyer 1992a;Semlitsch 1993), gives the hybrid a competitive advantage over the parent species. Yet the composition of natural water frog populations in terms of species frequencies among adults seems to be quite stable over time (Berger 1983).…”
Section: Introductionmentioning
confidence: 99%
“…A possible scenario follows. For some frog species it has been shown or suggested that tadpoles reduce activity in the presence of predators (Skelly & Werner, 1990;Semlitsch & Reyer, 1992;Anholt & Werner, 1999), thus reducing growth rate (Skelly, 1992;Laurila & Kujasalo, 1999). It is possible that low activity level is a ®xed trait for tadpoles from some ponds (and thus persisted when raised in tanks).…”
Section: Pond Effectsmentioning
confidence: 99%
“…This numerical superiority of the hybrid, plus the fact that R. esculenta females produce larger clutches than R. lessonae (Berger and Uzzell 1980;Reyer et al 1999), and R. esculenta larvae perform better than R. lessonae under most ecological conditions (Semlitsch and Reyer 1992;Semlitsch 1993 gives the hybrid a reproductive advantage. If mating were random, this would initially increase the hybrid's relative abundance in mixed populations, but in the long run it would dilute the parental species out of the population and, in the absence of the necessary sexual host, lead the hybrid to extinction, too.…”
Section: Introductionmentioning
confidence: 99%
“…Homotypic LR pairings produce RR tadpoles, but these usually die during the larval stage or shortly after metamorphosis, probably because of homozygosity of deleterious mutations that have accumulated on the clonally transmitted R genome (Berger 1977;Graf and Müller 1979;Semlitsch and Reyer 1992;Vorburger 2001;Guex et al 2002).…”
Section: Introductionmentioning
confidence: 99%